The six : the untold story of America's first women astronauts - Grush, Loren (Simon & Schuster for Young Readers, 2025)
"The extraordinary true story of America's first female astronauts hailed as "suspenseful, meticulously observed, enlightening" by Margot Lee Shetterly, #1 New York Times bestselling author of Hidden Figures, now adapted for young readers. Sally Ride may have been the first US woman in space, but did you know there were five other incredible American women who helped blaze the trail for female astronauts by her side? When NASA sent astronauts to the moon in the 1960s and 1970s, the agency excluded women from the corps, arguing that only military test pilots-a group women were also aggressively barred from-had the right stuff. But as the 1980s dawned so did new thinking, and six elite women scientists-Sally Ride, Judith Resnik, Anna Lee Fisher, Kathy Sullivan, Shannon Lucid, and Rhea Seddon-set out to prove they had exactly the right stuff to become the first US women astronauts. In The Six Young Readers Edition, acclaimed journalist Loren Grush shows how these brilliant and courageous women fought to enter STEM fields they were discouraged from pursuing, endured claustrophobic-and often deeply sexist-media attention, underwent rigorous survival training, and prepared for years to take multi-million-dollar equipment into orbit. Told with contributions from nearly all the living participants and now adapted for young readers, this book is an inspiring testament to their struggles, accomplishments, and sacrifices and how they built the tools that made the space program run. It's a legacy that lives on to inspire young people today"--